How can sustainability add value in destination marketing? the tourist perspective - Sita Dewi Kusumaningrum; Edza Aria Wikurendra; Marhadi Marhadi (Cogent Business & Management)
The link between sustainability and tourist value in the tourism sector remains unclear and contextual. In the current discourse, evaluation of sustainability value from the perspective of tourists (i.e. tourist-perceived value) has been limited. This paper thus investigates approaches to evaluating the tourist-perceived value of sustainability in the relevant literature, using marketing processes and the tourist destination sustainability strategy framework to understand how sustainability can add value in destination marketing. Analysing nine articles using the semi-systematic literature review method, three potential sources and approaches were identified: 1) in the segmentation process, 2) in the analysis of benefits and costs or willingness to pay, and 3) in the analysis of travellers’ emotions based on their experiences. All three approaches have strengths and weaknesses, and it is necessary to consider the context, time, and situation in selecting the correct approach—there is no one-size-fits-all solution. This paper proposes several considerations when selecting the most suitable approach to evaluate the tourist-perceived value of sustainability.